Jewish Philosophy and the Crisis of Modernity Essays and lectures in modern Jewish thought - Strauss, Leo; Green, Kenneth Hart (Albany (N. Y.) : State University of New York Press, 1997)
I. Essays in modern Jewish thought
II. Studies of modern Jewish thinkers
III. Lectures on contemporary Jewish issues
IV. Studies on the Hebrew Bible
V. Comments on Jewish history
VI. Miscellaneous whitings on jews and Judaism
VII. Autobiographical reflections.
Notes, bibliogr., index, append.